2013
DOI: 10.1073/pnas.1306241110
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived hydrogen sulfide, produced by cystathionine-β-synthase, stimulates bioenergetics, cell proliferation, and angiogenesis in colon cancer

Abstract: The physiological functions of hydrogen sulfide (H 2 S) include vasorelaxation, stimulation of cellular bioenergetics, and promotion of angiogenesis. Analysis of human colon cancer biopsies and patient-matched normal margin mucosa revealed the selective upregulation of the H 2 S-producing enzyme cystathionine-β-synthase (CBS) in colon cancer, resulting in an increased rate of H 2 S production. Similarly, colon cancer-derived epithelial cell lines (HCT116, HT-29, LoVo) exhibited selective CBS up-regulation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
723
4
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 655 publications
(767 citation statements)
references
References 46 publications
30
723
4
10
Order By: Relevance
“…Additionally, they shed light on the oligomerization and aggregation tendencies of this enzyme and reveal the distinct structural features in mammalian enzymes, such as hCBS, and those from other organisms, such as dCBS. More importantly, because hCBS represents a highly valuable therapeutic target for homocystinuria itself as well as for other conditions such as vascular disease and cancer (6,36), the data presented here pave the way for the rational design of inhibitors or activators modulating hCBS activity.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, they shed light on the oligomerization and aggregation tendencies of this enzyme and reveal the distinct structural features in mammalian enzymes, such as hCBS, and those from other organisms, such as dCBS. More importantly, because hCBS represents a highly valuable therapeutic target for homocystinuria itself as well as for other conditions such as vascular disease and cancer (6,36), the data presented here pave the way for the rational design of inhibitors or activators modulating hCBS activity.…”
Section: Discussionmentioning
confidence: 92%
“…Cystathionine-␤-synthase (CBS) and cystathionine-␥-lyase (CTH) are the main enzymes that catalyze the production of hydrogen sulfide, which plays essential roles in many pathological processes (41 ). It was reported that colon cancer cells selectively over-express CBS to maintain the cell bioenergetics and to support tumor growth (42 ). Moreover, the WNT pathway regulates the expression of CTH, which plays important roles in colon cancer (43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bioenergetic parameters were measured with XF24 Extracellular Flux Analyzer (Seahorse Bioscience) as described (12).…”
Section: Analysis Of Bioenergetic Parameters By Extracellular Flux Anmentioning
confidence: 99%